Active vibration control of a full scale aircraft wing using a reconfigurable controller. (20th January 2016) - Prakash, Shashikala; Renjith Kumar, T.G.; Raja, S.; Dwarakanathan, D.; Subramani, H.; Karthikeyan, C.
Abstract: This work highlights the design of a Reconfigurable Active Vibration Control (AVC) System for aircraft structures using adaptive techniques. The AVC system with a multichannel capability is realized using Filtered-X Least Mean Square algorithm (FxLMS) on Xilinx Virtex-4 Field Programmable Gate Array (FPGA) platform in Very High Speed Integrated Circuits Hardware Description Language, (VHDL). The HDL design is made based on Finite State Machine (FSM) model with Floating point Intellectual Property (IP) cores for arithmetic operations. The use of FPGA facilitates to modify the system parameters even during runtime depending on the changes in user's requirements. The locations of the control actuators are optimized based on dynamic modal strain approach using genetic algorithm (GA). The developed system has been successfully deployed for the AVC testing of the full-scale wing of an all composite two seater transport aircraft. Several closed loop configurations like single channel and multi-channel control have been tested. The experimental results from the studies presented here are very encouraging. They demonstrate the usefulness of the system's reconfigurability for real time applications.